A hybrid Protection Scheme based on Deep Reinforcement Learning - Kordowich, Georg; Jaworski, Michael; Lorz, Tobias; Scheibe, Christian; Jäger, Johann (2022 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT-Europe), 2022)
The growth of distributed renewable energy re-sources pushes classic protection schemes to their limits. An automated workflow is necessary to handle the volatility of future power systems characterized by constantly changing network states. Therefore a hybrid, deep reinforcement learning based protection scheme is proposed in this paper, which combines a single agent training for central protection with a multi agent training for a decentralized fallback.For this purpose, a training framework using a combination of PowerFactory and Python-Scripts connected via a Shared Memory is developed. The framework is used to train agents using Deep Recurrent Q-Learning. First a central protection is trained, which can then be imitated by decentral agents using only local measurements. Tests of the setup show a fast and selective response, which proves that deep reinforcement learning can indeed automatically generate a protection scheme fulfilling high requirements of dependability and security.<br

A Multi-Instance, Multi-Timestep Co-Simulation Approach for Power System Simulation Tools - Scheibe, Christian; Leugner, Johannes; Mehlmann, Gert; Luther, Matthias (2022 IEEE International Conference on Power Systems Technology: Embracing Advanced Technology in Power and Energy Systems for Sustainable Development, POWERCON 2022, 2022)
This paper proposes a Co-Simulation concept that couples two or more simulators utilizing different timesteps. The interprocess communication is handled via a shared memory based algorithm. Unfavorable effects due to the conversion between time steps are eliminated using filters. The electrical representation is based on a Bergeron line model utilizing the dependency of time and location of travelling waves along transmission lines. The proposed Co-Simulation has minimal impact on accuracy while greatly reducing simulation execution time.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Co-Simulation; Electromagnetic Transients; Shared Memory; Transmission Line Models

Analysis of Different Latencies and Time Delays in a Coupled Power-Hardware-in-the-Loop Laboratory - Wagner, Timo; Richter, Julian; Scheibe, Christian; Resch, Simon; Mehlmann, Gert; Luther, Matthias (EPEC 2022, 2022)

A Novel Co-Simulation Concept using Interprocess Communication in Shared Memory - Scheibe, Christian; Raab, Alexander; Semerow, Anatoli; Menke, Jasmin; Mehlmann, Gert; La Seta, Piergiovanni; Luther, Matthias (2019 IEEE Power & Energy Society General Meeting (PESGM), 2019)

Concept and Operation of a distributed multi-domain Power System Laboratory with HiL-capabilities - Mehlmann, Gert; Scheibe, Christian; Resch, Simon; Kordowich, Georg; Richter, Julian; Wagner, Timo; Kuri, Ananya; Richter, Michael; Jäger, Johann; Luther, Matthias (ETG-Fachbericht 170: ETG Kongress 2023, 2023)

Integration of an EMT HVDC model into a Transient Stability Study using Co-Simulation - Scheibe, Christian; Richter, Michael; Raab, Alexander; Stopfer, Benedikt; Mehlmann, Gert (IEEE PES Innovative Smart Grid Technologies Conference Europe, 2022)
This paper provides insights into the development and application of coupling power system models within different simulation domains (phasor and instantaneous values) in a multi-instance manner using Co-Simulation. Overcoming the challenge of integrating a PSCAD modeled modular multilevel converter into the transient stability test model known as Nordic Test System, the Co-Simulation interface development and implementation process is laid out. Hybrid simulations are performed to verify the model and to investigate grid stabilizing effects of the converter in the RMS power system model. Results prove to the Co-Simulation to be a viable option, practically eliminating the need to re-model an existing EMT subsystem for this kind of studies.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Co-Simulation; EMT; HVDC; MMC; RMS

Interfacing real-time and offline power system simulation tools using UDP or FPGA systems - Scheibe, Christian; Kuri, Ananya; Feng, Yuyao; Zhao, Le; Xiong, Xuejun; La Seta, Piergiovanni; Liang, Xiao Peng; Knödtel, Johannes; Holzinger, Philipp; Reichenbach, Marc; Mehlmann, Gert (Electric Power Systems Research, 2022)
This contribution proposes a coupling interface between the real-time simulation system RTDS Novacor and the Power System Simulation Software PSS/E for electromagnetic transient (EMT) and phasor (RMS) hybrid simulations to enable a performant connection between the domains. For the coupling interface, two implementations with different characteristics in latency and hardware requirements are presented. Firstly, an Ethernet (UDP) based connection and secondly a fiber-based connection using the Aurora protocol. The first approach is purely software based, while the second one requires additional hardware. The technical implementation of the interfaces is explained in detail. The functionality of the interfaces is verified on the basis of an EMT-RMS simulation in a small overhead line test system.
CRIS-Team WoS Importer:2022-10-14

Real Time Co-Simulation of Electromechanical and Electromagnetic Power System Models - Scheibe, Christian; Kuri, Ananya; Graf, Lorenz; Venugopal, Ravinder; Mehlmann, Gert (SEST 2022 - 5th International Conference on Smart Energy Systems and Technologies, 2022)
The goal of the paper is to demonstrate the feasibility of a real-time co-simulation of electromechanical /root-mean-square (RMS) and electromagnetic transient (EMT) power system models. For this purpose, a co-simulation framework has been developed along with a benchmark system for establishing boundary conditions for RMS-EMT modeling and co-simulation. For the co-simulation, a real-time machine of OPAL-RT has been coupled with another real-time simulator from the manufacturer RTDS Technologies Inc. The OPAL-RT simulator operates in RMS and EMT modes, whilst the RTDS simulator runs in EMT. An optimized low-latency high-speed optical fiber interface is developed to realize the co-simulation of the two modes across the two platforms. The Nordic Test System is used as an exemplary test network to create one part of the co-simulated network. Insights into modeling of discrete-continuous power systems are described and boundary conditions established to ensure accurate modeling for the different timescales and domains. Numerical results from a real-time co-simulation of a high-voltage direct current (HVDC) link running in EMT mode on the RTDS coupled with a model of the Nordic 32 Test System in RMS mode on the OPAL-RT simulator under fault conditions are presented.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Co-simulation; EMT; Nordic32; real-time simulation; RMS

Transformation, Comparison and Co-Simulation of a RMS-EMT Multi-Domain Test Network - Schweinshaut, Bernd; Scheibe, Christian; Mehlmann, Gert; Luther, Matthias (Conference on Sustainable Energy Supply and Energy Storage Systems, 2022)